The Rebirth of Philosophy - Ding, Jian (Journal of NeuroPhilosophy, 2026)
There is continuity between truth and the relevant objective things in reality, and its intrinsic mechanism is inertia. Inertia is an inherent characteristic of objective things, and truth resides there. Inertia generates continuity, which is a necessary condition for reasoning. It can go from the quantitative change of real space all the way deep into the qualitative change of the ideal realm, and expand the philosophical view of materialism to the category of metaphysics. In the fundamental part of Eastern and Western philosophy, this absence has been for more than two thousand years. From this, it can be seen that the law of the unity of opposites should have been Trialism. In fact, we use it every day, yet do not reflect on it deliberately. Once a consensus is reached, it means the unification of Eastern and Western philosophies. Based on this, the norms for identifying truth are given, and the true nature of metaphysics is restored through norms and definitions. In addition, the definition of philosophy is discussed and given. The Trialism on things' limits is founded, which resolves the dilemma that truth has no place in Dualism, and thereby uses this theory to perfect materialism as well as the unity of opposites of all knowledge.